Role of Social Media in Agricultural Knowledge Dissemination: Perspectives from Tharu Farmers Residing in Tikapur Kailai, Nepal (Panauti Journal, 2025)
Social media integration into agricultural operations has emerged as a transformative force in agricultural development, with Nepalese farmers increasingly adopting these platforms. This study assesses the role of social media in agricultural knowledge dissemination among Tharu farmers in Tikapur (Block 32), Kailali District, Sudurpashchim Province, Nepal, using a descriptive and explanatory research design with cross-sectional survey methods. Data were collected from 50 participating farmers via self-administered semi-structured questionnaires to evaluate adoption rates, platform preferences, and perceived utility. Analysis through MS Excel revealed varied digital engagement: while most respondents regularly use social media, Facebook, YouTube, and WhatsApp dominate the digital landscape, with Twitter and LinkedIn showing minimal uptake. Farmers expressed mixed perceptions, ranging from optimism to skepticism, about social media's impact on agricultural practices. Findings indicate that farmers primarily use these platforms for information sharing and problem-solving rather than commercial applications, highlighting untapped economic potential. To maximize benefits, the study recommends that local governments implement digital literacy programs, develop localized agricultural content in native languages, improve rural digital infrastructure, and foster public-private partnerships to create farmer-friendly marketplaces—all while integrating these initiatives with traditional knowledge systems to empower smallholder farmers. The study implies that policies enhancing digital literacy, localized content, and infrastructure are key to leveraging social media for Tharu farmers’ agricultural development.